STRATEGI INTEGRATED MARKETING COMMUNICATION (IMC) DALAM MENDAPATKAN RESELLER DARI AGROWING.CO.ID - Frisca Arta Mulia (Universitas Mercu Buana, 2020)
This research was conducted to determine the Integrated Marketing Communication (IMC) Strategy to Reach Resellers from Agrowing.co.id.The paradigm used in this thesis is the post-positivist paradigm and uses a qualitative approach with descriptive research type, data collection techniques through interviews. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses source triangulation. The results of this thesis indicate that the integrated marketing communication strategy (IMC) chosen is able to get a reseller from Agrowing.co.id. In planning an integrated marketing communication strategy, Agrowing.co.id used SWOT Analysis, STP analysis, Target audience Determination, Media Selection, and Determination of the Mixture of Marketing Communication Elements. In its activities Agrowing.co.id used all integrated marketing communication (IMC) which is advertising, sales promotion, public relations, personal selling, interactive marketing, and direct marketing. The most effective integrated marketing communication strategies are interactive marketing, personal selling, and sales promotion. Suggestion according to researchers is to strengthen the marketing element mix that is advertising so that integrated marketing communication strategies are more optimal. As well as adding human resources to optimize integrated marketing communication.